Cassava Production Efficiency in Southern Ethiopia: The Parametric Model Analysis - Tafesse, Alula; Mena, Bekele; Belay, Abrham; Aynekulu, Ermias; Recha, John W.; Osano, Philip M.; Darr, Dietrich; Demissie, Teferi D.; Endalamaw, Tefera B.; Solomon, Dawit (Frontiers in Sustainable Food Systems, 2021)
This research article estimates the cassava production efficiency level and investigates determinants of the inefficiency in southern Ethiopia. A systematic questionnaire was used to collect cross-sectional data from 158 households. The Cobb-Douglas (CDs’) stochastic frontier production model was used to measure the levels of production efficiency. The computed mean result indicated the echnical efficiency (TE), allocative efficiency (AE), and economic efficiency (EE) levels of 74%, 90%, and 66%, respectively. This showed that the existing farm resources could improve the average production efficiency levels by 26.43%, 10.01%, and 33.92%, respectively. The analysis confirmed that land size, urea fertilizer application, and cassava planting cut had a positive and significant effect on the production of cassava. We found that TE was more important than AE for EE as a source of benefit. Inefficiency effects modeled using the two-limit Tobit model showed that the most important factors for improving TE, AE, and EE efficiencies were household head age, level of education, cassava variety, extension contact, rural credit, off-farm activities involvement to generate income, and farm size. Therefore, to address inefficiency in cassava production, policy makers in government should consider these factors. Particularly it requires availing appropriate agricultural knowledge through short-term training, farmers access to formal education, accessing improved cassava varieties, and supporting agricultural extension services.